319 Occupational exposures in veterinarians: findings from a national surveillance project (CAREX Canada). (11th October 2013) - Hall, L; Peters,; Davies,; Demers,
Abstract : Objectives: Veterinarians work in a variety of environments with diverse patient types. Risk of physical injury and zoonoses are common concerns for this group, but other exposures may also produce adverse health outcomes. The objective of this study was to identify Canadian veterinary exposure prevalence and levels for ionising radiation (IR) and antineoplastic agents (AAs), as part of the CAREX Canada project. Methods: For IR, we used 2008 whole-body dose data from a national government exposure registry. Veterinarians with measured levels of exposure were identified. The proportions exposed were combined with 2011 national veterinary statistics to estimate the prevalence range within two exposure categories. For AAs, prevalence and exposure category estimates were formed by combining the 2011 national veterinary statistics with information on practice type and AA usage rates obtained from provincial veterinary associations, peer-reviewed literature, and veterinary field experts. Results: In 2008, 26% of Canadian veterinarians were monitored for IR exposure. Of the 3, 155 veterinarians monitored, 282 (8.9%) had a dose >0 mSv. Extrapolating to all veterinarians in Canada, we estimate a maximum of 1070 are exposed to IR doses above zero mSv. The majority (n = 278–1055) fall within a low dose category (>0–1mSv) while n = 4–15 are exposed to levels between 1–5 mSv. None had doses >5 mSv. We estimate that 18% of veterinarians (n = 2, 200) are exposed to AAs; these fall into two categories of moderate exposure, defined as "low frequency, low control" (n = 2, 180) and "high frequency, high control" (n = 20). Conclusions: CAREX Canada's exposure estimates could be used to assist in the development of epidemiological studies or risk assessments. Our estimates indicate that exposure to IR and AAs in veterinarians is low, however the accuracy of our findings is limited by data sources of varying quality. We plan to refine our current estimates and assess other exposures in veterinary settings.